Tumor progression is associated with increasing CD11b+ cells and CCL2 in Lewis rat sarcoma - Mishra, Rajbardhan; Kovalska, Jana; Janda, Jozef; Vannucci, Luca; Rajmon, Radko; Horak, Vratislav (Anticancer research, 2015)
Tumor models are essential for basic anticancer research and development of novel therapies. In this study, we used a rat sarcoma model in which subcutaneous tumor develops after D6 cell inoculation. The aim of the current study was to analyze changes in haematological parameters, immune cell sub-populations and cytokine profiling during tumor growth, after tumor excision and after second inoculation of D6 cells. Tumor progression was found to be associated with an increased number of leukocytes and increased proportion of CD11b+ cells in peripheral blood. Serum concentration of chemokine (c-c motif) ligand 2, L-selectin and intra cellular adhesion molecule-1 also increased with growing tumor. However, the proportion of CD4+, CD8+ and MHC II+ cells decreased with growth of tumors. After tumor excision, all these parameters returned to pre-inoculation levels and did not change even after a second inoculation of D6 cells. Moreover, absence of secondary tumors after second inoculation of D6 cells gives an insight into development of antitumor immunity stimulated by primary tumor.
Keywords: CD11b Antigen; CCL2; progrese nemoci; Chemokine CCL2; tumor immunology; chemokin CCL2; Lewis rat sarcoma; antigeny CD11b; Disease Progression; Flow Cytometry; krysa rodu Rattus; průtoková cytometrie; Animals; neutrophils; zvířata; Rats, Inbred Lew; Rats; Sarcoma, Experimental; leukocytóza; CD11b+ cells; potkani inbrední LEW; Leukocytosis; experimentální sarkom